Biodegradation and environmental impact of kenaf fiber water filters: Towards sustainable water purification solutions - Sadiq, Umar Abubakar; Yelwa, Jibrin Muhammad; Michael, Bello Oluwasesan (International Journal of Chemistry and Materials Research, 2025)
This study evaluates the efficacy of kenaf fiber water filters with particular emphasis on filtration efficiency, biodegradability, and structural properties. Characterization techniques such as Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDX), X-ray Diffraction (XRD), and Thermogravimetric Analysis (TGA) have been employed to analyze the fibers. The investigation compares untreated and chemically treated kenaf fibers regarding their ability to remove contaminants including turbidity, nitrate, phosphate, Total Dissolved Solids (TDS), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD). FTIR analysis indicated that chemical treatment modifies certain functional groups, enhancing water resistance of the fibers. SEM-EDX results showed that treated fibers are more porous and possess smoother surfaces, which improve their capacity to trap contaminants effectively. XRD analysis revealed a significant increase in the fibers’ crystallinity index from 44.3% in untreated fibers to 76.87% in treated fibers contributing to enhanced filtration performance. TGA confirmed that treated fibers exhibit greater thermal stability, with degradation temperatures rising from 240°C to 280°C. When compared to synthetic and ceramic filters, kenaf-based filters are environmentally friendly and cost-effective. The filters demonstrated high removal efficiencies, such as 99.98% for turbidity, 96.85% for phosphate, and 92.76% for chlorine. A notable advantage of kenaf fibers is their biodegradability, as they disintegrate within 90 days, thereby reducing environmental impact over time. Despite ongoing challenges related to durability and large-scale production, these findings suggest that kenaf is a promising and sustainable option for water filtration applications.